WORKING WITH SURGICAL EQUIPMENT, VARIOUS SUTURING AND TYING TECHNIQUES (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
This article delves into the intricate world of surgical techniques, focusing on the art and science of suturing and tying. With a detailed exploration of various methods, this comprehensive guide aims to provide insights into the significance of mastering these skills in the contemporary medical landscape. The article combines annotation, keywords, and a thorough analysis of existing literature to offer a valuable resource for surgeons, medical professionals, and aspiring practitioners.